Y : the last man. Unmanned - Vaughan, Brian K. (DC Comics, 2025)
"After Man. In 2002, the world changes forever. Every man, every boy, every mammal with a Y chromosome everywhere on Earth suddenly collapses and dies. With the loss of more than half the planet's population, the gears of society grind to a halt, and a world of women are left to pick up the pieces and try to keep civilization from collapsing entirely. The "gendercide," however, is not absolutely complete. For some unknown reason, one young man named Yorick Brown and his pet male monkey, Ampersand, are spared. Overnight, this anonymous twentysomething becomes the most important person on the planet-the key to unlocking the secret of the mysterious sex-specific plague. Y: The Last Man Book One features writer Brian K. Vaughan and artist Pia Guerra bringing to life their amazing answer to the age-old speculation: What would really happen to the last man on Earth?"-- Provided by publisher.